Aspects of Urbanization in China Shanghai, Hong Kong, Guangzhou - Bracken, Gregory (Amsterdam University Press, 2012)
China's rise is one of the transformative events of our time. Aspects of Urbanization in China: Shanghai, Hong Kong, Guangzhou examines some of the aspects of China's massive wave of urbanization - the largest the world has ever seen. The various papers in the book, written by academics from different disciplines, represent ongoing research and exploration and give a useful snapshot in a rapidly developing discourse. Their point of departure is the city - Shanghai, Hong Kong and Guangzhou - where the downside of China's miraculous economic growth is most painfully apparent. And it is concern for the citizens of these cities that unifies the papers in a book whose authors seek to understand what life is like for the people who call them home.